2019
DOI: 10.1071/en19049
|View full text |Cite
|
Sign up to set email alerts
|

Multilayered surface for the interactive separation of perchlorate from aqueous medium

Abstract: Environmental contextPerchlorate from rocket fuel plants or firework manufacturing units can seriously contaminate drinking water. We developed a separation skin on a microfiltration membrane and on sand that can remove perchlorate from water in the presence of competing ions. This method is suitable for a domestic water purification unit selective for perchlorate removal. AbstractThis study reports an interactive separation of perchlorate (ClO4−) by polyethyleneimine (PEI) and poly (styrene sulfonate) (PSS) d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Meanwhile, the LBL-based NF membrane performance could also be compromised in strong alkaline conditions due to the deprotonation of amine groups of the weak cationic polyelectrolytes . This was witnessed by the decline in ClO 4 – rejection of the (PEI/PSS) 9 membrane from above 80% to ∼16% after subjecting to pH 10 solution . In this study, the PEI molecules were covalently bonded with PDA via Michael addition and Schiff base reactions. , The covalent bonds and cross-linking between PDA and PEI restricted the movement of PEI chains to a certain extent and significantly improved the chemical stability of the membrane.…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations
“…Meanwhile, the LBL-based NF membrane performance could also be compromised in strong alkaline conditions due to the deprotonation of amine groups of the weak cationic polyelectrolytes . This was witnessed by the decline in ClO 4 – rejection of the (PEI/PSS) 9 membrane from above 80% to ∼16% after subjecting to pH 10 solution . In this study, the PEI molecules were covalently bonded with PDA via Michael addition and Schiff base reactions. , The covalent bonds and cross-linking between PDA and PEI restricted the movement of PEI chains to a certain extent and significantly improved the chemical stability of the membrane.…”
Section: Resultsmentioning
confidence: 87%
“…It has been reported that in the conventional LBL assembly system, the polyelectrolyte multilayers formed with weak cationic polyelectrolytes such as PAH and PEI might suffer from significant swelling in the strong acid conditions due to strong electrostatic repulsion between protonated amine groups, which influenced both the chemical and physical integrity of the multilayers . For example, after exposure to pH 4 solution for 30 min, the flux of the (PEI/PSS) 9 membrane (nine bilayers) increased by 31%, ascribing to the structural rearrangement of the polyelectrolyte multilayers . Meanwhile, the LBL-based NF membrane performance could also be compromised in strong alkaline conditions due to the deprotonation of amine groups of the weak cationic polyelectrolytes .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is found to be an effective method to enhance the removal efficiency of low pressure–driven membranes. Suitability of polyelectrolyte multilayer membranes in ion removal was well studied in the past, and the efficiency of these membranes to remove ions at lower energy expense is commendable (Cheng et al., 2018; Disha et al., 2012; Liu et al., 2017; Sahin et al., 2020; Sanyal et al., 2015; Shalumon et al., 2019).…”
Section: Introductionmentioning
confidence: 99%